Concentric Circles and Spiral Configurations for Large Correlator Arrays in Radio Astronomy - Kiehbadroudinezhad, Shahideh; Cada, Michael; Chen, Zhizhang (David); Shahabi, Adib; Short, C. Ian; Abidin, Zamri Zainal; Kiehbadroudinezhad, Samiramis (IOP Publishing, 2018)
Aperture synthesis arrays are commonly used in radio astronomy to take images of radio point sources, with the planned Square Kilometre Array (SKA) being the most common example. One approach to enhancing the quality of the images is to optimize an antenna array configuration in a possible SKA implementation. An ideal arrangement must ensure optimal configurations to capture a clear image by either decreasing the sidelobe level (SLL) in the l-m domain or increasing the sampled data in the spatial-frequency domain. In this paper a novel configuration is considered to optimize the array by considering all possible observation situations through the positions of the antenna array elements via a mathematical model that we call geometrical method (GM). To demonstrate its efficiency, the technique is applied to developing an optimal configuration for the elements of the Giant Metrewave Radio Telescope (GMRT). The effect of these changes, particularly in the forms of circular and spiral arrangements, is discussed. It is found that a spiral configuration results in fewer overlapping samples than the number of antennas placed along three arms of the GMRT with fewer than 11% and 27% overlapping samples in the snapshot and 6 hr tracking observations, respectively. Finally, the spiral configuration reduces the first SLL from -13.01 dB, using the arms of the current GMRT configuration, to -15.64 dB.